Comparative transcriptomic analysis of Clostridium perfringens biofilms and planktonic cells. Issue 5 (2nd September 2016) - Charlebois, Audrey; Jacques, Mario; Archambault, Marie
ABSTRACT: Clostridium perfringens is an opportunistic pathogen that can cause food poisoning in humans and various enterotoxaemias in animal species. Recently, C. perfringens was shown to form biofilms, a structured community of bacterial cells enclosed in a self-produced extracellular matrix. However, very little is known on the subject and no information is available on gene expression in C. perfringens biofilms. To gain insights into the differences between free-living C. perfringens cells and those in biofilms, we used RNA sequencing. In total, 25.7% of genes showed differential expression in the two growth modes; about 12.8% of genes were up-regulated and about 12.9% were down-regulated in biofilms. We show that 772 genes were significantly differentially expressed between biofilms and planktonic cells from the supernatant of biofilms. Genes that were down-regulated in biofilm cells, relative to planktonic cells, included those involved in virulence, energy production, amino acid, nucleotide and carbohydrate metabolism, and in translation and ribosomal structure. Genes up-regulated in biofilm cells were mainly involved in amino acid and carbohydrate metabolism, transcription, inorganic ion metabolism and in defence mechanisms. This study provides new insights into the transcriptomic response of C. perfringens during biofilm formation.